ANALISIS KELAYAKAN PENGEMBANGAN USAHA "LAODE GALERI'' DI MAKASSAR - Laode Muh Syawal; Muhammad Hidayat; Fitriani Latief (Jurnal Bisnis dan Kewirausahaan, 2020)
The purpose of this study is to analyze the feasibility of aspects of non-financial and financial Gallery. The data analysis method used is qualitative (legal aspects, social and econonomic aspects, technical aspects, market aspects and marketing and management aspects. Whereas financial analysis for the feasibility of financial aspects uses quantitative analysis (present value, net present value, profitability index, payback period, internal rate of return, the average rate of return). To find out whether or not a business is feasible and which will be carried forward. The results of the study indicate that the Laode Gallery business of the non financial aspect is feasible to run from the legal aspects, social and economic aspects, technical aspects, market aspects and marketing and management aspects. And the results of the analysis of the financial aspects of the next 10 years show Laode gallery through a present value analysis of 761.395.342.-, the net present value of Rp. 143,465,342.-, 27% profitability index, 17% internal rate of return, 6 years 7 months payback period, while the average rate of return obtained during the prediction of the next 10 years is 26%.